Immunohistochemical analysis of extracellular signal-regulated kinase expression in mature and immature bulls' testes and epididymides - S Jang; C Yun; B Kim; S Kang; J Lee; S Jeong; Y Cho; K Sung-Ho; L Chang-Min; C Moon; K Joong-Sun (Veterinární Medicína, 2023)
Extracellular signal-regulated kinase (ERK) has been implicated in mammalian testicular and epididymal development. This study aimed to investigate ERK expression in the immature and mature testes and epididymides of bulls. We evaluated ERK expression using immunoblot analysis and immunohistochemistry. Immunoblot analysis revealed that immature bull testes and epididymides had higher phosphorylated ERK (pERK) expression than mature bull testes and epididymides. pERK immunoreactivity was higher in immature epididymides than in immature testes. pERK was localised mostly in spermatogonia, undifferentiated sustentacular (Sertoli) cells, and interstitial (Leydig) cells in immature testes, as well as in some spermatocytes and spermatids in mature testes. In immature epididymides, the body and tail had higher pERK expression than the head, whereas pERK was broadly distributed throughout the stereocilia, basal cells, and connective tissues. pERK distribution in the head of mature epididymides was similar to that in immature epididymides, whereas few connective tissue cells were expressed in the body and tail of mature epididymides. Collectively, these results suggest that ERK is expressed in the testis and epididymis of immature and mature bulls with varying intensities, and the role of ERK in male reproductive organs may include the specific function of its development.